13 C hyperpolarization with nitrogen-vacancy centers in micro- and nanodiamonds for sensitive magnetic resonance applications - Blinder, Rémi; Mindarava, Yuliya; Korzeczek, Martin; Marshall, Alastair; Glöckler, Felix; Nothelfer, Steffen; Kienle, Alwin; Laube, Christian; Knolle, Wolfgang; Jentgens, Christian; Plenio, Martin B.; Jelezko, Fedor (Science advances, 2025)
Nuclear hyperpolarization is a known method to enhance the signal in nuclear magnetic resonance (NMR) by orders of magnitude. The present work addresses the 13 C hyperpolarization in diamond micro- and nanoparticles, using the optically pumped nitrogen-vacancy center (NV) to polarize 13 C spins at room temperature. Consequences of the small particle size are mitigated by using a combination of surface treatment improving the 13 C relaxation ( T 1 ) time, as well as that of NV, and applying a technique for NV illumination based on a microphotonic structure. Adjustments to the dynamical nuclear polarization sequence (PulsePol) are performed, as well as slow sample rotation, to improve the NV- 13 C polarization transfer rate. The hyperpolarized 13 C NMR signal is observed in particles of 2-micrometer and 100-nanometer median sizes, with enhancements over the thermal signal (at 0.29-tesla magnetic field) of 1500 and 940, respectively. The present demonstration of room-temperature hyperpolarization anticipates the development of agents based on nanoparticles for sensitive magnetic resonance applications. Nuclear hyperpolarization of 13 C spins is performed at ambient conditions in micro- and nanodiamonds.